Information Disclosure and Demand Elasticity of Financial Products : Evidence from a Multi-Country Study - Gine, Xavier; Martínez Cuellar, Cristina; Mazer, Rafael Keenan (World Bank, Washington, DC, 2017)
This study tests the effectiveness of behavioral-based disclosure formats. Around 1,700 individuals from Mexico and Peru chose among loans and savings accounts presented in different formats, including a simplified key facts statement (KFS) and current marketing brochures. The study finds that the price elasticity of loans is -1.04 using brochures and -3.19 using the simplified KFS, with smaller effects for savings products. Finally, while financial literacy is correlated with better decision-making, the effect of the disclosure format for loans is about three times as large as that of financial literacy. More importantly, the KFS helps financially illiterate individuals relatively more.